Pengelolaan Usaha Kerajinan Bedeg Bali - Ni Luh Putu Ening Permini; Made Ayu Desy Geriadi; I Gusti Made Sudika; Made Ratna Witari; Ni Ketut Sukanti (KREATIF: Jurnal Pengabdian Masyarakat Nusantara, 2023)
Craft business is a business that is carried out by selling various handicraft products that have functions and economic value. Many Indonesian people have been involved in the craft industry, one of which is the bedeg craft industry, in Bali. However, during the implementation process, bedeg entrepreneurs experienced many obstacles such as a lack of ability to prepare financial report books, lack of marketing outreach, and a bedeg design that seemed to be monotonous. The purpose of implementing this trial is to help partners, namely Bedeg Sudiana Craftsmen, to overcome the problems they face. The process of implementing the program is carried out by carrying out 3 service activity programs including providing assistance and assisting in making bookkeeping and financial reports, making social media and providing assistance and assisting in product design development. The results of the implementation of this activity show that the partners are very enthusiastic in participating in the training and that there is an increase in the ability of partners to manage finances. In addition, with the training activities, the reach of partner businesses has become wider, resulting in an increase in the number of product orders. Partners hope that this service activity can be carried out in a sustainable manner because it can have a positive influence on business progress.